2023
DOI: 10.3389/fpubh.2023.1194779
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of school-based exercise interventions on physical fitness in children and adolescents: a systematic review and network meta-analysis

Abstract: BackgroundSchools provide a favorable setting for health education, however, the most effective school-based exercise mode for improving physical fitness remains unclear. This network meta-analysis was designed to assess and rank the comparative efficacy of six exercise modalities on physical fitness indicators in a school-based setting.MethodsAn online search of the Web of Science, PubMed, SPORTDiscus, and Scopus databases was conducted. Randomized and quasi-randomized controlled trials were considered. Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 121 publications
0
4
0
1
Order By: Relevance
“…The benefits of physical education intervention programs on children’s physical fitness are well documented [ 24 ]. Regarding possible confounding variables, such as age, sexual maturation, and weight status, evidence suggest that different youth populations does not benefit themselves equally from school-based intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of physical education intervention programs on children’s physical fitness are well documented [ 24 ]. Regarding possible confounding variables, such as age, sexual maturation, and weight status, evidence suggest that different youth populations does not benefit themselves equally from school-based intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A common benefit from physical education intervention programs for children is the improvement of cardiorespiratory fitness [ 24 ]. Also, intervention programs seem to consistently increase children’s MVPA during physical education lessons in addition to their physical fitness [ 11 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a la velocidad aláctica, se ha observado que las intervenciones escolares fundamentales pueden mejorar significativamente la capacidad de sprint (Wu et al, 2023). Esta observación podría explicar, al menos en parte, por qué en el estudio presente solo el CC mostró una mejora significativa en la prueba de sprint de 20 metros, siendo los menores resultados del GE posiblemente atribuida a la variabilidad de la base, lo que podría haber limitado el margen de mejora debido al principio de especificidad en la carga de trabajo (Kasper, 2019).…”
Section: Discussionunclassified
“…Some research has indicated that physical activity not only mitigates health issues related to MetS, including adiposity and inflammation, but also strengthens physical fitness, bone health, and cognitive performance [33,34]. School-based intervention studies have reported that physical activity is associated with improvements in physical fitness, muscle strength, and cardiorespiratory fitness [35]. The World Health Organization has published guidelines on physical activity for children and adolescents [36].…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%